2015
DOI: 10.1016/j.cub.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Lycaenid Caterpillar Secretions Manipulate Attendant Ant Behavior

Abstract: Mutualistic interactions typically involve the exchange of different commodities between species. Nutritious secretions are produced by a number of insects and plants in exchange for services such as defense. These rewards are valuable metabolically and can be used to reinforce the behavior of symbiotic partners that can learn and remember them effectively. We show here novel effects of insect exocrine secretions produced by caterpillars in modulating the behavior of attendant ants in the food-for-defense inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 24 publications
(36 reference statements)
1
53
0
Order By: Relevance
“…Thus, the unambiguous identification of a manipulation event requires an understanding of the physiological and molecular mechanisms that cause these alterations. In other words, the observation of a manipulation effect does not suffice to characterize the manipulator as a parasite (Heil, 2015), because manipulation effects can also be exerted by mutualists (Wright et al, 2013;Heil et al, 2014;Hojo et al, 2015). Only the demonstration that a certain phenotypic alteration in the host is under the genetic control of the parasite and that it enhances the fitness of the parasite vi an enhancement of its transmission rate, while decreasing the fitness of the host, would provide clear evidence in favor of adaptive host manipulation.…”
Section: Future Stepsmentioning
confidence: 99%
“…Thus, the unambiguous identification of a manipulation event requires an understanding of the physiological and molecular mechanisms that cause these alterations. In other words, the observation of a manipulation effect does not suffice to characterize the manipulator as a parasite (Heil, 2015), because manipulation effects can also be exerted by mutualists (Wright et al, 2013;Heil et al, 2014;Hojo et al, 2015). Only the demonstration that a certain phenotypic alteration in the host is under the genetic control of the parasite and that it enhances the fitness of the parasite vi an enhancement of its transmission rate, while decreasing the fitness of the host, would provide clear evidence in favor of adaptive host manipulation.…”
Section: Future Stepsmentioning
confidence: 99%
“…Strikingly, Hojo et al also reported an enhanced aggressiveness of manipulated ants. This behavioural change was associated with altered dopamine levels in the brains of the ants, albeit ants that had access to DNO secretions contained lower, rather than higher levels of dopamine [1]. The different directions in the changes in dopamine levels in manipulated mammals and ants clearly represent an interesting research subject per se.…”
mentioning
confidence: 96%
“…In a new ground breaking study Hojo et al [1] report partner manipulation for an interaction that previously was considered to be a reward-for-defence mutualism. Lycaenid caterpillars secrete a metabolically valuable liquid from their dorsal nectary organ (DNO) and are tended by ants, which feed on this reward and defend the caterpillar against predators.…”
mentioning
confidence: 99%
See 2 more Smart Citations